Phe(475) and Glu(446) but not Ser(445) participate in ATP-binding to the alpha-subunit of Na(+)/K(+)-ATPase - Kubala, Martin; Hofbauerová, Katerina; Ettrich, Rüdiger; Kopecký, Vladimír; Krumscheid, Rita; Plásek, Jaromír; Teisinger, Jan; Schoner, Wilhelm; Amler, Evzen (Biochemical and biophysical research communications, 2002)
The ATP-binding site of Na(+)/K(+)-ATPase is localized on the large cytoplasmic loop of the alpha-subunit between transmembrane helices H(4) and H(5). Site-directed mutagenesis was performed to identify residues involved in ATP binding. On the basis of our recently developed model of this loop, Ser(445), Glu(446), and Phe(475) were proposed to be close to the binding pocket. Replacement of Phe(475) with Trp and Glu(446) with Gln profoundly reduced the binding of ATP, whereas the substitution of Ser(445) with Ala did not affect ATP binding. Fluorescence measurements of the fluorescent analog TNP-ATP, however, indicated that Ser(445) is close to the binding site, although it does not participate in binding.
Keywords: adenosintrifosfát; sodíko-draslíková ATPasa; Fluorescent Dyes; Recombinant Fusion Proteins; vazebná místa; fenylalanin; Phenylalanine; Protein Subunits; rekombinantní fúzní proteiny; podjednotky proteinů; molekulární modely; Glutamic Acid; Models, Molecular; Binding Sites; Animals; Sodium-Potassium-Exchanging ATPase; konformace proteinů; zvířata; fluorescenční barviva; myši; Adenosine Triphosphate; Protein Conformation; Mice; Serine; kyselina glutamová; serin